New Insights in Transcriptional Regulation of the Ethylene Response in Arabidopsis - Wang, Likai; Qiao, Hong (Frontiers in Plant Science, 2019)
As any living organisms, plants must respond to a wide variety of environmental stimuli. Plant hormones regulate almost all aspects of plant growth and development. Among all the plant hormones, ethylene is the only gaseous plant hormone that plays pleotropic roles in plant growth, plant development and stress responses. Transcription regulation is one main mechanism by which a cell orchestrates gene activity. This control allows the cell or organism to respond to a variety of intra- and extracellular signals and thus mount a response. Here we review the progress of transcription regulation in the ethylene response.